Pengaruh Kepemilikan Asing, Direktur dan Komisaris Asing Terhadap Penghindaran Pajak dimoderasi oleh Profitabilitas - Yustia, Lisa; Khomsiyah, Khomsiyah (Universitas Batanghari Jambi, 2024)
The purpose of this research is to examine the impact of foreign ownership, foreign directors and commissioners on the company's efforts to avoid tax liabilities, taking into account the role of profitability as a moderating factor. The Data used came from 44 companies in the energy sector listed on the Indonesia Stock Exchange in the period 2020-2022. Sampling was carried out through systematic random methods, and regression analysis with the concept of modernization was used to process the data. The findings of this research illustrate that foreign ownership and foreign directors and commissioners have an impact on tax avoidance practices in the corporate environment. It added that the profitability factor plays a crucial role in regulating the relationship between tax evasion and foreign ownership. In more detail, profitability has the potential to amplify the impact of foreign ownership on tax avoidance practices. On the other hand, the profitability factor also has no effect in moderating the relationship between foreign directors and commissioners against tax evasion practices.